Factors associated with teacher militancy in Metro Manila - Reodique, Luis P. 1930-
The respondents include 1,080 teachers and 126 school administrators from all levels in all 126 schools. Teacher militancy is positively related to those (1) who voted for the opposition candidate in the February 7, 1986 "Snap" election, (2) whose administrator favors teacher strikes, (3) whose parents have pro-union sentiments, (4) who cherish "bahala na" attitude, (5) with high social awareness, (6) who own a house and lot appliances, facilities in Metro Manila, and (7) who did not vote during the "Snap" election. Teacher militancy is also significantly related to family gross annual income; length of work experience; and the male teachers. No significant relationship exists between teacher militancy and teacher aspiration and attitude towards work, age, educational attainment, civil status, employment status, work load, religion, GSIS/SSS institution benefits received, economic security, nationalism, size, facilities and location of school.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Teachers' socio-economic status -- Philippines -- Manila metropolitan area; Strikes and lockouts -- Teachers -- Philippines -- Manila metropolitan area